Butyrophilin controls milk fat globule secretion - Robenek, Horst (National Academy of Sciences, 2006)
The molecular mechanism underlying milk fat globule secretion in mammary epithelial cells ostensibly involves the formation of complexes between plasma membrane butyrophilin and cytosolic xanthine oxidoreductase. These complexes bind adipophilin in the phospholipid monolayer of milk secretory granules, the precursors of milk fat globules, enveloping the nascent fat globules in a layer of plasma membrane and pinching them off the cell. However, using freeze-fracture immunocytochemistry, we find these proteins in locations other than those previously inferred. Significantly, butyrophilin in the residual plasma membrane of the fat globule envelope is concentrated in a network of ridges that are tightly apposed to the monolayer derived from the secretory granule, and the ridges coincide with butyrophilin labeling in the globule monolayer. Therefore, we propose that milk fat globule secretion is controlled by interactions between plasma membrane butyrophilin and butyrophilin in the secretory granule phospholipid monolayer rather than binding of butyrophilin–xanthine oxidoreductase complexes to secretory granule adipophilin.